2014
DOI: 10.1089/brain.2013.0214
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and Discriminative Subnetwork Mining for Mild Cognitive Impairment Classification

Abstract: Recent studies on brain networks have suggested that many brain diseases, such as Alzheimer's disease and mild cognitive impairment (MCI), are related to a large-scale brain network, rather than individual brain regions. However, it is challenging to find such a network from the whole brain network due to the complexity of brain networks. In this article, the authors propose a novel method to mine the discriminative subnetworks for classifying MCI patients from healthy controls (HC). Specifically, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 77 publications
0
27
0
1
Order By: Relevance
“…The construction of the hyper-networks enabled us to identify the interaction information among brain regions. In addition, to show that the classification method based on subgraph features can better capture the topological information among brain regions, Fei et al ( 2014 ) adopted frequent subgraph mining technology to mine frequent sub-networks in an MCI dataset, then used a discriminative subgraph mining algorithm to mine discriminative sub-networks. Finally, they used SVM based on a graph kernel for the classification.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the hyper-networks enabled us to identify the interaction information among brain regions. In addition, to show that the classification method based on subgraph features can better capture the topological information among brain regions, Fei et al ( 2014 ) adopted frequent subgraph mining technology to mine frequent sub-networks in an MCI dataset, then used a discriminative subgraph mining algorithm to mine discriminative sub-networks. Finally, they used SVM based on a graph kernel for the classification.…”
Section: Discussionmentioning
confidence: 99%
“…Yetkin et al ( 2006 ) confirmed that AD was more active in the right middle frontal gyrus, left inferior temporal gyrus, left thalamus, and right lenticular putamen nucleus than the NC. Fei et al ( 2014 ) showed the difference of topological structures between the MCI, and NC were mainly in left rolandic operculum, insula, left supplementary motor area, left hippocampus, left parahippocampal gyrus, right parahippocampal gyrus, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the multi-kernel SVM was used to classify the two groups of subjects. Fei et al ( 2014 ) had constructed threshold connectivity networks of NC and MCI, and extracted frequent subgraphs, and subsequently selected a discriminative subgraph as a feature. Finally, SVM was used for the classification.…”
Section: Discussionmentioning
confidence: 99%
“…脑网络一般表示为矩阵形式, 如何有效地抽取网络特征, 并利用其对不同被试进行比较一直是脑 网络分析的热点问题. 在以往的研究中, 研究者多使用网络连接边权重、频繁模式, 以及一些图论中的 经典度量方法 [23,24] , 但是这些方法并不能完整反映网络的整体特性. 因此在网络的特征表示问题上, 我们提出了一种使用有序子图模式来表示脑网络的方法 [25] , 其中有序子图模式是由一系列成对的由 权值边组成的序关系构成, 具体如图 5 所示.…”
Section: 脑网络构建及特征表示unclassified